Advances in ergonomic design of systems, products and processes : proceedings of the annual meeting of GfA 2016 - Schlick, Christopher Marc; Duckwitz, Sönke; Flemisch, Frank; Frenz, Martin; Kuz, Sinem; Mertens, Alexander; Mütze-Niewöhner, Susanne (Springer, 2017)
These proceedings summarize the best papers in each research area represented at the 2016 Annual Meeting of the German Human Factors and Ergonomics Society, held at Institute of Industrial Engineering and Ergonomics of RWTH Aachen University from March 2-4. The meeting featured more than 200 presentations and 36 posters reflecting the diversity of subject matter in the field of human and industrial engineering. This volume addresses human factors and safety specialists, industrial engineers, work and organizational psychologists, occupational medicines as well as production planners and design engineers.
Keywords: Human engineering -- Congresses.; Human-robot interaction -- Congresses.; elektronické knihy; electronic books